PENGEMBANGAN MEDIA SMART BOX PADA SISWA KELAS IV UNTUK MENINGKATKAN KEMAMPUAN MENULIS PARAGRAF DESKRIPSI DALAM MATA PELAJARAN BAHASA INDONESIA - Tri Atmojo; Kiswoyo; Lina Putriyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The background that drives this research is that in the process of learning indonesian language subjects, teachers have not utilized media optimally, causing students to become less enthusiastic and quickly get bored in the learning process. The objectives of this research are (1) To determine and describe the suitability of Smart Box concrete media in improving listening skills in Indonesian language lessons. (2) To find out and describe the effect of using Smart Box concrete media on learning outcomes in the Indonesian language learning process for class IV SD Negeri 2 Tejorejo Kendal. This type of research is research and development using the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). This research and development produces products in the form of interactive learning media that have gone through a validation process from material experts, media experts, and teacher responses. The results of validation by material experts obtained a percentage of 91%, media experts showed a percentage of 85%, and the results of the teacher response questionnaire obtained a percentage of 94% with "very good" criteria. Based on the research results, it can be seen that interactive concrete object learning media is declared very suitable for use as supporting media in the Indonesian language learning process in class IV at SDN 2 Tejorejo Kendal.